Tomografía computada craneoencefálica como métodos diagnóstico en niños menores de 5 años: uso racional, idicaciones y cumplimiento de la recomendación N° 26 del ICRP sistema de protección radiológica esteblecido por la Comisión Internacional de protección radiológica en el Área de Imagen del Hospital General Isidro Ayora en el periodo comprendido entre el 9 de enero al 9 de julio del 2014 - Cueva Medina, Pablo Ismael (2015)
This study is a prospective study with quantitative and descriptive aspects with a transversal cut, with the principle objective of verifying if the CAT scan is used in a rational form as a diagnostic method for children under five years of age. Two important aspects were evaluated: a strong justification based on diagnosis and plan written by treating physicians, and the dosage of radiation is also evaluated, to confirm if Radiology personal in the General Hospital of Loja apply the lowest dose possible to reach optimization. 122 CAT scans in total are evaluated; the principle motive of requesting the CAT scan was Traumatic Brain Injury, to evaluate the integrity of the skull and brain. Similarly, a principle motive to request CAT scan was the precedent of head trauma with or without symptoms and/or signs. Although the CAT scans that were performed presented pathological findings in only 5%, all CAT scans used higher doses of radiation than the recommended dose, without implementing modifications in the dose for children. In conclusion, CAT scan is not used in rational form and ALARA principles are not complied. Key words - CAT: Computed axial tomography - HGIA: General Hospital of Loja - Justification, optimization y dose limitation